Segmentation of esports audience and its marketing implications - Sagl, Dominik (2022)
This thesis provides a detailed segmentation of the esports audience. From a theoretical view, the study gives a complex overview of esports as a global phenomenon. The practical part focuses on the segmentation in which a survey was conducted gathering 373 responses that were afterwards used in the clustering analysis. The clustering was conducted using a number of clustering methods, and the optimal method was then selected based on statistical and subjective evaluations. K-Means was selected as the optimal approach for creating clusters, which were then examined from an interpretation standpoint. Two clusters were found by K-means which were significantly different based on psychographic, demographic, and behavior data from the survey. These segments were thoroughly explained to provide a comprehensive picture of the clusters. In addition, a series of suggestions that should considerably boost a company's esports success was developed based on the study's findings and theoretical research.